The Therapy of Burn Wound Healing in Rat (Wistar) by Using the Combination of Peripheral Blood Mononuclear Cells (PBMCs) and Bone Marroe BM-Derived Mesenchymal Stem Cell - Gusti Revilla (Stem Cell Research and Development Center, Universitas Airlangga, 2021)
The therapy to heal the bum wound is still imperfect, therefore it is important to conduct specific research concerning this topic that benefits to society. Using both Bone Marrow-stem cell (BM-MSc) and peripheral blood mononuclear cells (PBMCs) from allogenic donors as part of the therapy to heal the bum wound seems to give positive prospect for the future treatment. In this experiment, PBMC and rat BM- derived from mesenchymal stem cell were used as the therapy model. lmmunocytochemistry was used as the method to characterize the phenotype of MSc, It was also used to express the collagen type I and the Indirect ELISA in analyzing the TGF·P 1 secretion. The rats with bum wound were divided into 2 kinds of group; the first group of rats was selected to control the use of PBS; while second group of rats was used as the treatment object that was medicated by the applying of the combination of both BM-MSC and PBMC. Stem-cells subcutaneously administered dose applied to each rat was around of 2 x 106 cells. The result showed that the levels of TGF-β1 secretion in day 3rd and day 7th on the rats which were treated by using the combination of BM-MSC and PBMC were higher compared to the rats from the control group. The experiment that concerns on the thickness of the collagen showed that combination between BM-MSC and PBMC stem cell make it possible in increasing the thickness of collagen 1, besides; it also showed significant differences (p=0.000). This research proved that the combination of BM-MSC and PBMC stem cell served can accelerate the healing process for the bum wound on rats through Increasing of TGF-P 1 secretion and collagen type 1 expression, It means that PBMCs can be applied as good as chemoattractant.